INTERNALISASI NILAI MODERASI BERAGAMA PADA SANTRI PONDOK PESANTREN AL-MAZAYA PASER KABUPATEN PASER PROVINSI KALIMANTAN TIMUR - Mardani, Mardani; Siswanto, Siswanto (PAI RAFAH, 2024)
Indonesia, as a majority-Muslim nation, has become a focal point for several countries and a primary focus in the context of religious moderation. Therefore, it is crucial for us to comprehend the principles of religious moderation, which play a pivotal role in Islam. Profound knowledge of religion obtained through educational institutions like boarding schools and madrasah, along with the effective role of scholars and kiai as exemplars of religious behavior, aids in upholding stability in religious comprehension within Indonesian society. Boarding school stands as one among various religious institutions, serving the dual function of imparting, understanding, and deepening Islamic teachings, as well as disseminating religious knowledge to society. The boarding school AL-Mazaya Paser implements a curriculum that integrates general education with pesantren education, allowing for the effective internalization of values of religious moderation and contributing to the development of knowledge within the pesantren. This study utilizes a qualitative descriptive approach, aiming to elucidate the circumstances or phenomena observed in the field based on collected data, narrated in words or sentences, categorized to draw conclusions and provide solutions to emerging issues, supported by empirical data at boarding school Al-Mazaya Paser. By applying pesantren and madrasah curricula and operating under the supervision of the Ministry of Religious Affairs in Kabupaten Paser, boarding school Al-Mazaya Paser integrates boarding school education with formal and boarding school curricula. Furthermore, this boarding school adheres to the principle of “Religious Moderation” as a genuine embodiment of the institution’s vision and mission